2004
DOI: 10.1210/me.2003-0414
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicle Development Requires Smad3

Abstract: Smad3 is an important mediator of the TGF beta signaling pathway. Interestingly, Smad3-deficient (Smad3-/-) mice have reduced fertility compared with wild-type (WT) mice. To better understand the molecular mechanisms underlying the reduced fertility in Smad3-/- animals, this work tested the hypothesis that Smad3 deficiency interferes with three critical aspects of folliculogenesis: growth, atresia, and differentiation. Growth was assessed by comparing the size of follicles, expression of proliferating cell nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 79 publications
4
77
1
2
Order By: Relevance
“…Smad3Ϫ͞Ϫ mice, which are defective in the expression of Smad3 in all tissues, also have a bone phenotype with an osteopenic reduction in bone volume (14,17). In addition to the direct role of TGF-␤͞Smad3 signaling in bone metabolism, some aspects of the Smad3Ϫ͞Ϫ bone phenotype may be due to immune, gastrointestinal, or endocrine defects associated with systemic loss of Smad3 expression (24)(25)(26). No gross abnormalities have been reported in Smad3ϩ͞Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smad3Ϫ͞Ϫ mice, which are defective in the expression of Smad3 in all tissues, also have a bone phenotype with an osteopenic reduction in bone volume (14,17). In addition to the direct role of TGF-␤͞Smad3 signaling in bone metabolism, some aspects of the Smad3Ϫ͞Ϫ bone phenotype may be due to immune, gastrointestinal, or endocrine defects associated with systemic loss of Smad3 expression (24)(25)(26). No gross abnormalities have been reported in Smad3ϩ͞Ϫ mice.…”
Section: Resultsmentioning
confidence: 99%
“…The similarly increased bone mass, mineral concentration, and mechanical properties in DNT␤RII and Smad3ϩ͞Ϫ bones stand in contrast to the phenotypes of D4 and D5 bones with increased TGF-␤ signaling ( Table 1). The Smad3Ϫ͞Ϫ bone phenotype likely combines bone-specific, i.e., increased osteoblast apoptosis (14), and progressive secondary effects of systemic Smad3 absence on the bone metabolism and health of the mice as mentioned above (24)(25)(26).…”
Section: Tgf-␤ Signaling Regulates Bone Mineral Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the SMAD signal transduction proteins are known to mediate signaling by members of the TGF-β superfamily, which is involved in the control of normal folliculogenesis and ovulation [7,8], and they associate with members of the Forkhead family of transcription factors, the FOXO class [34], thought to play important roles in oocyte maturation, ovulation, and possibly luteinization [34][35][36][37][38][39], with expression in human granulosa cells [40], it is possible that SMAD expression levels may also affect ovarian folliculogenesis and fertility. Female Smad3 −/− mice exhibit impaired folliculogenesis and reduced fertility [28,30] and Smad4 ovarian-specific knockout mice exhibit multiple defects in folliculogenesis and decreased fertility over time [27]. Female mice in which dominant negative Smad2 is expressed in granulosa cells exhibit impaired folliculogenesis and the females are subfertile [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ovarian-and granulosaspecific Smad knockout and transgenic mouse models exhibit a variety of defects in folliculogenesis, coupled with reduced fertility [26][27][28][29][30]. In humans, transcripts for SMAD2, 3 and 4 have been identified in granulosa cells collected at oocyte retrieval [31], which suggested that these and other SMADs might also be involved in human ovarian function and fertility.…”
Section: Introductionmentioning
confidence: 99%